A Case Series of 18 Patients Receiving Ticagrelor After Carotid Stenting. (October 2018) - Olafson, Elizabeth M.; DeGrote, Jodi R.; Drofa, Alexander; Kouznetsov, Evgueni; Manchak, Michael; Leedahl, Nathan D.; Leedahl, David D.
Purpose: Dual antiplatelet therapy (DAPT) with aspirin and a P2Y12 receptor antagonist is often used to prevent thrombotic complications after endovascular stent placement. Most of the published experience surrounding DAPT after carotid stenting is with clopidogrel. Ticagrelor may be a promising alternative, especially in patients who may be considered nonresponders to clopidogrel. However, clinical outcomes utilizing DAPT with ticagrelor in a cohort with carotid stenting is lacking. In this case series, we describe our experience with systematic prescribing of ticagrelor after carotid stent placement in 18 patients. Methods: A retrospective review of 18 patients prescribed ticagrelor who underwent carotid stenting between November 2015 and January 2017 was performed. All eligible patients were included in the review. The primary end point of interest was any ischemic stroke or death within 30 days following the procedure. Intracranial hemorrhage was a secondary end point. Results and Conclusions: No patients experienced the primary end point of ischemic stroke or death within 30 days. No intracranial hemorrhages were observed. The use of ticagrelor after carotid stenting may be a reasonable alternative to clopidogrel after carotid stent placement. Randomized trials to support our findings are needed.